Highly linear inductorless asymmetric capacitive cross-coupled wideband balun-LNAs. (May 2020) - K, Hari Kishore; Sat, Prakash; B, Kasi Raju; B, Venkataramani
Abstract: Two Inductorless balun low noise amplifiers (LNAs- LNA1, LNA2) are proposed in this paper to reduce the noise figure (NF) and improve the linearity. They use asymmetric capacitive cross-coupling (A-CCC) and auxiliary CS amplifier to reduce the NF. Robust derivative superposition is used in LNA2 to improve the 3rd order input intercept point, and hence the linearity. The proposed A-CCC balun-LNAs are implemented in 0.18 µm CMOS technology, and their performances are evaluated through post-layout simulations, PVT variation analysis and Monte Carlo simulations. From these studies, the average NF, gain and the 3dB-bandwidths of LNA1 and LNA2 obtained are (2.49 dB, 20 dB, 0.1–2.48 GHz) and (2.61 dB, 19.8 dB, 0.1–2.0 GHz) respectively. For a 1.2 V supply and an area of 0.02mm 2, the power consumption of LNA1 and LNA2 are 4.9 mW and 5.8 mW, respectively. The performances of the proposed LNAs are also compared with other wideband LNAs reported in the literature.